Combining Ecological Niche Models and ecosystem services indicators to assess impacts of climate change on kelp: application to French coasts - Jules Pecquet; Maud Mouchet; Sylvie Campagne; Virginie Raybaud; Yoann Baulaz; François Gevaert; Frida Ben Rais Lasram (Ecosystems and People, 2022)
Kelp forests, primarily Laminaria digitata, provide a broad range of ecosystem services of high social, economic, and ecological value and are considered one of the most productive ecosystems on the planet. Several studies have shown that kelp ecosystems are regressing in response to multiple stressors, especially climate change, which could lead to local extinctions. This may induce a decrease in the ecosystem services provided. Many studies use ecological niche models (ENM) to project potential future species distributions under climate change scenarios; however, no study has projected the future supply of ecosystem services resulting from shifts in species ranges and changes in biomass. In this study, using French coasts as a case study, we developed a new and reproducible methodological framework that combines ENM and ecosystem services indicators to assess impacts of climate change on ecosystem services supplied by kelp. To this end, we first identified ecosystem services currently provided by kelp and then used ENM to project future kelp distribution from 2041 to 2050 under climate scenarios RCP2.6 and RCP8.5. Finally, by estimating the biomass of kelp, we assessed the current and future ecosystem services provided by kelp.